Evaluasi Pelatihan Program Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka Menggunakan Model Kirkpatrick di SDN 1 Gerung Utara - Mia Tri Ardene; Pusfita Hunaeda; Istiharah; Nur Aulia Hidayatni; Candra (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to evaluate the effectiveness of differentiated instruction training in the implementation of the Merdeka Curriculum using the Kirkpatrick Model. The study employs a mixed-methods approach with a sequential explanatory design, which integrates quantitative and qualitative data in stages. The research subjects’ teachers in SDN 1 Gerung Utara who participated in differentiated learning training. Data collection was conducted through questionnaires, tests, observations, interviews, and documentation, which were analyzed based on the four Kirkpatrick levels: reaction, learning, behavior, and results. The results of this study indicate that the differentiated learning training was generally deemed effective in enhancing teachers’ competencies and the quality of learning at SDN 1 Gerung Utara. At the reaction level, the training received a very positive response with an average of 86.25%, indicating that the lessons were highly relevant and engaging. This was followed by concrete knowledge gains at the learning level, evidenced by an increase in the average posttest score from 64.22 on the pretest to 82.10, which falls into the moderate N-Gain category. This improvement is not merely theoretical; it also impacts teachers’ teaching practices. This is particularly true for managing heterogeneous classrooms, with an 85% success rate. More broadly, this training has significantly increased student engagement, fostered more varied learning experiences, and improved overall student learning outcomes. Teachers also reported feeling more confident in creating flexible lesson plans aligned with the Merdeka Curriculum. The study concluded that the behavioral changes and outcomes achieved must be sustained through further mentoring and institutional support, even though the results were already quite positive.